1985
DOI: 10.1172/jci111760
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke can activate the alternative pathway of complement in vitro by modifying the third component of complement.

Abstract: Cigarette smoking is associated with significant increases in the number of pulmonary mononuclear phagocytes and neutrophils. A potent chemoattractant for these cells is C5a, a peptide generated during complement (C) activation. We, therefore, investigated the possibility that cigarette smoke could activate the complement system in vitro. Our results show that factor(s) (mol wt < 1,000) present in an aqueous solution of whole, unfiltered cigarette smoke can deplete the hemolytic capacity of whole human serum i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 31 publications
1
74
0
1
Order By: Relevance
“…The present study did not investigate if the observed complement activation was due to tobacco smoke-induced oxidant damage to EC. In addition, given the short half life of the reactive thioester bond in C4b [41], it has not been possible to determine whether the observed increase in EC surface C4d reflects TS induced fluid phase complement activation [14,15] with subsequent binding of C4b to EC surfaces, or enhanced classical pathway complement activation by EC affected by TS. In either case, complement activation on or near EC will contribute to vascular inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study did not investigate if the observed complement activation was due to tobacco smoke-induced oxidant damage to EC. In addition, given the short half life of the reactive thioester bond in C4b [41], it has not been possible to determine whether the observed increase in EC surface C4d reflects TS induced fluid phase complement activation [14,15] with subsequent binding of C4b to EC surfaces, or enhanced classical pathway complement activation by EC affected by TS. In either case, complement activation on or near EC will contribute to vascular inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoke has been described to induce plasma chemotaxins and anaphylatoxins, C3a and C5a [14]. Moreover, Kew et al [15] reported that tobacco smoke extract modifies C3 in vitro, leading to activation of the alternative complement pathway. We postulate that complement activation on altered vascular endothelial cells serves both protective and pathologic functions.…”
Section: Introductionmentioning
confidence: 99%
“…Cigarette smoke has been shown to activate the alternative complement pathway through the modification of C3 in vitro (56). Similar processes acting in vivo could promote inflammatory events at the RPE-choroid interface in the eye that hasten drusen formation and exacerbate the genetic susceptibility to AMD that is conferred by the at-risk HF1 haplotype.…”
Section: Biological Model Of Hf1 Dysfunction In Amdmentioning
confidence: 99%
“…42 Cigarette smoke has been shown to activate C3 in vitro and makes it less susceptible to inactivation by CFH and CFI. 43 In vivo, tobacco activates the classical pathway. 44 AREDS reported that high dietary intake of omega-3 long chain polyunsaturated fatty acids was associated with lower risk of neovascular AMD.…”
Section: Environmental Exposure and Complementmentioning
confidence: 99%